A solidifying material and solidifying method suitable for rapidly improving the early strength of high-water content sludge
By using specific proportions of admixtures and main curing materials in high moisture content sludge for flocculation and dehydration and two-stage curing, the problems of poor curing effect and low early strength in the existing technology are solved, and efficient curing and resource utilization are achieved.
Patent Information
- Application Number
- CN202411191645.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-28
AI Technical Summary
The existing cured materials have poor curing effect on dredging sludge with high moisture content and high organic matter rivers, low early strength, and difficult to use in resource use.
The admixture consisting of magnesium silicate, aluminum sulfate, polymeric iron sulfate, ammonium sulfate and quicklime is combined with the main curing material composed of blast furnace slag, steel slag, calcium carbide slag and phosphogypsum. The two-stage curing of sulfate is stimulated through flocculation and dehydration and alkali-excited sulfate excitation, promoting the rapid generation of ettringite and C-S-H.
The early strength of high moisture content sludge is significantly improved, and the unbounded compressive strength of 3d and 7d can be increased by 1.5 to 2.0 times, meeting the requirements of rapid construction and resource utilization of crushed compacted soil.
Smart Images

Figure CN118993499B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sludge resource utilization, and in particular to a solidifying material and a solidifying method suitable for rapidly improving the early strength of sludge with a high water content. Background Art
[0002] In order to improve river water quality, ensure river flood discharge capacity and smooth waterways and ports, a large amount of river dredging silt is generated every year. Usually, river dredging adopts hydraulic suction method, and the silt produced has ultra-high water content, extremely poor engineering properties, and a high content of organic matter in the silt. How to economically and effectively dispose of river dredging silt with ultra-high water content is a problem widely concerned by all sectors of society today.
[0003] Silt solidification treatment is to add a solidifying agent to reduce the water content of silt and change the physical and chemical properties of silt, thereby converting waste silt into excellent filling materials for water conservancy, roads, water transportation and other projects. Therefore, solidification treatment of river dredged silt not only solves the problems of land occupation and water and soil pollution, but also realizes the resource utilization of waste silt, which has great social and economic value.
[0004] However, it should be pointed out that for river dredged silt with high water content and high organic matter content, conventional solidification materials usually have poor solidification effect, large dosage, and high carbon emissions, such as cement and lime-based solidifiers. Therefore, for river dredged silt with high water content, it is urgent to develop new green solidification materials that are economical, effective and environmentally friendly. In addition, for the crushing and compaction construction method of solidified soil, most of the existing new solidification materials are used. The strength of the silt at the age of 28 days after solidification can usually meet the requirements of crushing and rolling construction, but the early strength within 3 to 7 days is difficult to reach the design strength target, which greatly prolongs the early curing time of solidified silt, which not only reduces the efficiency of crushing and compaction of solidified silt, but also requires sufficient yards for curing in the project, resulting in a significant increase in the construction cost of the project. Summary of the invention
[0005] The purpose of the present invention is to provide a solidifying material and a solidifying method suitable for quickly improving the early strength of high-water content sludge, so as to solve the engineering problems that the existing solidifying materials have poor solidification effect, low early strength and great difficulty in resource utilization for high-water content, high-organic matter river dredged sludge, and greatly improve the early strength of high-water content solidified sludge.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is to provide a sludge solidification material, which comprises an admixture and a main solidification material;
[0008] The raw materials of the admixture include, by weight: 18 to 20 parts of magnesium silicate, 15 to 18 parts of aluminum sulfate, 10 to 13 parts of polyferric sulfate, 22 to 26 parts of ammonium sulfate and 24 to 26 parts of quicklime;
[0009] Calculated by weight, the raw materials of the main solidifying material include: 50-70 parts of blast furnace slag, 5-10 parts of steel slag, 15-25 parts of carbide slag and 8-15 parts of phosphogypsum.
[0010] The mass of the admixture is 3-4 wt % of the mass of the main curing material.
[0011] Furthermore, the admixture is obtained by mixing magnesium silicate, aluminum sulfate, polyferric sulfate, ammonium sulfate and quicklime according to a mass ratio; the main solidifying material is obtained by mixing blast furnace slag, steel slag, carbide slag and phosphogypsum according to a mass ratio.
[0012] The second technical solution of the present invention is to provide the application of the above-mentioned sludge solidification material in the solidification of high-water content sludge, wherein the water content of the high-water content sludge is 100-600wt%, and the organic matter content is 10-15wt%.
[0013] In the present invention, the moisture content of sludge is defined by soil mechanics: moisture content = mass of water in soil / mass of dry soil.
[0014] The third technical solution of the present invention is to provide a method for solidifying sludge with a high water content, using the above-mentioned sludge solidification material, the method comprising the following steps:
[0015] The admixture is obtained by mixing magnesium silicate, aluminum sulfate, polyferric sulfate, ammonium sulfate and quicklime according to a mass ratio;
[0016] The main solidifying material is obtained by mixing blast furnace slag, steel slag, carbide slag and phosphogypsum according to a mass ratio;
[0017] The admixture is added to the high-water content sludge, and stirred for 10 to 15 minutes to obtain pre-treated sludge, and then the main solidification material is added to the pre-treated sludge for curing to achieve solidification of the high-water content sludge;
[0018] The high-water content sludge has a water content of 100-600wt% and an organic matter content of 10-15wt%.
[0019] Furthermore, the addition amount of the main solidifying material is 5-15wt% of the wet soil mass in the high-water content sludge.
[0020] Furthermore, the curing temperature is 15-30°C, and the relative humidity is >85%.
[0021] Furthermore, when the moisture content of the high-moisture sludge is greater than 160wt% and less than or equal to 600wt%, the admixture is added to the high-moisture sludge, stirred for 10 to 15 minutes, allowed to stand for 5 to 10 minutes to separate the mud and water, the supernatant is extracted to obtain pretreated sludge, and then the raw materials of the main solidifying material are added to the pretreated sludge and cured to achieve solidification of the high-moisture sludge.
[0022] The present invention is based on the design concept of first rapid flocculation and dehydration and then solidification. It first uses admixtures for flocculation and dehydration, and then uses industrial waste slag (blast furnace slag, steel slag, carbide slag and phosphogypsum) for the second stage of solidification, thereby developing a new type of green solidification material and solidification method with good solidification effect and high early strength to meet the needs of resource utilization of river silt with high water content.
[0023] The working principle of the curing material of the present invention is:
[0024] When the solidifying material with the proportion described in the present invention is used to solidify the dredged sludge in a river channel with a high water content, the sludge is first flocculated and dehydrated by adding an admixture, wherein the aluminum sulfate, polyferric sulfate and quicklime in the admixture flocculate suspended particles to form floccules; ammonium sulfate reacts with water to generate sulfuric acid, and magnesium silicate reacts with sulfuric acid to generate magnesium sulfate and colloidal silicon dioxide, wherein the generated magnesium sulfate utilizes ion exchange and electrical neutralization to aggregate fine suspended particles and small floccules into larger clusters, thereby accelerating their precipitation or coagulation into solid matter, and the generated colloidal silicon dioxide utilizes its strong adsorption and bridging performance to make fine and loose floccules and clusters coarse and dense, thereby accelerating the precipitation and dehydration of the sludge; in addition, by applying the admixture, the aluminum ions, calcium ions, sulfate ions and the like introduced into the sludge can promote the formation of calcium sulfonate in the subsequent solidification stage, and the magnesium ions and iron ions have a complexing adsorption effect on the heavy metal ions in the sludge, and have a stabilizing effect on the heavy metal ions in the sludge. Afterwards, an industrial waste slag-based solidifying agent is added to the sludge after flocculation and dehydration, wherein carbide slag and steel slag are alkali activators, and phosphogypsum is a sulfate activator. The alkali and sulfate activations jointly promote the depolymerization and dissolution of active silica and active alumina in blast furnace slag. At the same time, the aluminum ions and sulfate ions introduced in the flocculation and dehydration stage promote the rapid formation of calcium sulfonate, and the silicate ions in the admixture can also accelerate the formation of CSH, thereby improving the early strength of the solidified sludge.
[0025] The present invention first utilizes silicate, aluminum salt and iron salt composite admixtures for flocculation and dehydration, first reduces the free water content in river sludge, and simultaneously introduces aluminum ions, calcium ions, sulfate ions and the like that can promote the rapid generation of ettringite, and then utilizes an industrial waste slag-based curing agent with blast furnace slag, steel slag, carbide slag and phosphogypsum as main components to promote the rapid generation of ettringite and CSH, thereby achieving a substantial improvement in the early strength of the solidified sludge.
[0026] The present invention discloses the following technical effects:
[0027] (1) The admixture of the present invention is a mixture of magnesium silicate, aluminum sulfate, polyferric sulfate, ammonium sulfate and quicklime, wherein the aluminum sulfate, polyferric sulfate and quicklime in the admixture accelerate the formation of flocculants by agglomerating suspended particles; ammonium sulfate reacts with water to generate sulfuric acid, and magnesium silicate reacts with sulfuric acid to generate magnesium sulfate and colloidal silica, the generated magnesium sulfate utilizes ion exchange and electrical neutralization to aggregate fine suspended particles into larger clusters, promoting precipitation and coagulation into solid matter, and the generated colloidal silica has a strong adsorption and bridging function, which can make the flocculants become coarse and dense, thereby accelerating the flocculation, precipitation and dehydration of sludge; in addition, by adding the admixture, the aluminum ions, calcium ions, sulfate ions and the like introduced into the sludge can promote the formation of calcium sulfonate in the subsequent solidification stage, and the magnesium ions and iron ions have a complexing and stabilizing effect on the heavy metal ions in the sludge.
[0028] (2) The main solidifying material of the present invention is mainly composed of blast furnace slag, steel slag, carbide slag and phosphogypsum, wherein steel slag and carbide slag are used as alkali activators, and phosphogypsum is used as sulfate activator to jointly stimulate the depolymerization and dissolution of active silica and active alumina in blast furnace slag, thereby promoting the rapid formation of calcium sulfoxide, and at the same time, the introduced silicate ions are used to accelerate the formation of CSH, thereby improving the early solidification effect of dredging high water content rivers through synergistic effects.
[0029] (3) The present invention adopts a two-stage application method of an admixture and a curing agent. First, an admixture is used to flocculate and precipitate the high-water content sludge, and aluminum ions, calcium ions, sulfate ions, etc. are introduced to promote the formation of calcium aluminate. Then, the main curing material is used to solidify the sludge after flocculation and dehydration. The 3d and 7d unconfined compressive strength of the solidified sludge treated by this method can be increased by 1.5 to 2.0 times compared with when no admixture is added. It can meet the requirements of rapid construction and resource utilization of crushed and compacted soil of solidified sludge, and has significant engineering value. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is an electron microscope scanning image of the sample of the solidified material prepared in Example 1 of the present invention after curing for 3 days. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] In the following examples of the present invention, the blast furnace slag, steel slag, carbide slag, and phosphogypsum (calcium sulfate dihydrate) used are all industrial waste residues, and the remaining raw materials are all commercially available products.
[0038] Example 1
[0039] A solidifying material suitable for rapidly improving the early strength of high-water content sludge, comprising an admixture and a main solidifying material. The raw material composition is shown in Table 1. The water content of the high-water content river sludge is 120wt%, and the organic matter content is 7.5wt%.
[0040] Solidification process of high water content river silt:
[0041] (1) mixing magnesium silicate, aluminum sulfate, polyferric sulfate, ammonium sulfate and quicklime according to a mass ratio to obtain the admixture;
[0042] (2) mixing blast furnace slag, steel slag, carbide slag and phosphogypsum according to a mass ratio to obtain the main solidifying material;
[0043] (3) Add the admixture to the high-water content river silt, stir for 10 minutes, then add the main curing material, stir evenly, pour into a mold, and prepare a cylindrical sample with a diameter of 50 mm and a height of 100 mm. After 24 hours, demould, wrap with plastic wrap, and place in an environment with a temperature of 20°C and a humidity of 90% for curing. Among them, the admixture dosage is 3.0wt% of the main curing material dosage, and the main curing material is 8.0wt% of the mass of the wet soil of the high-water content river silt.
[0044] The electron microscope scanning image of the sample in this embodiment after 3 days of curing is as follows: Figure 1 As shown in the figure, a large number of needle-shaped, overlapping calcium sulfonate crystals are generated in the early solidified sludge. At the same time, a large number of foil-shaped and fibrous CSH are also generated, which are intertwined and attached to form a three-dimensional space that is firmly combined and dense, effectively improving the early strength of the solidified sludge.
[0045] Example 2
[0046] A solidifying material suitable for rapidly improving the early strength of high-water content sludge, comprising an admixture and a main solidifying material. The raw material composition is shown in Table 1. The water content of the high-water content river sludge is 120wt%, and the organic matter content is 7.5wt%.
[0047] The solidification process and maintenance of high-water content river silt are the same as in Example 1.
[0048] Example 3
[0049] A solidifying material suitable for rapidly improving the early strength of high-water content sludge, comprising an admixture and a main solidifying material. The raw material composition is shown in Table 1. The water content of the high-water content river sludge is 260wt%, and the organic matter content is 15.0wt%.
[0050] Solidification process of high water content river silt:
[0051] (1) mixing magnesium silicate, aluminum sulfate, polyferric sulfate, ammonium sulfate and quicklime according to a mass ratio to obtain the admixture;
[0052] (2) mixing blast furnace slag, steel slag, carbide slag and phosphogypsum according to a mass ratio to obtain the main solidifying material;
[0053] (3) Add the admixture to the high-water content river sludge, stir for 10 minutes, then let it stand for 8 minutes for flocculation and dehydration, and remove the supernatant after the mud and water are separated; then, add the main curing material, stir evenly, pour it into a mold, and prepare a cylindrical sample with a diameter of 50 mm and a height of 100 mm. After 24 hours, demould it, wrap it with plastic wrap, and put it in an environment with a temperature of 20°C and a humidity of 90% for curing. Among them, the amount of the admixture is 4.0wt% of the amount of the main curing material, and the main curing material is 15.0wt% of the mass of the wet soil of the high-water content river sludge.
[0054] Comparative Example 1
[0055] The only difference from Example 3 is that ammonium sulfate is omitted in the admixture.
[0056] Comparative Example 2
[0057] The only difference from Example 2 is that steel slag is omitted from the main solidifying material.
[0058] Comparative Example 3
[0059] The only difference from Example 2 is that carbide slag is omitted in the main solidifying material.
[0060] Comparative Example 4
[0061] The only difference from Example 1 is that no admixture is added, and the flocculation and dehydration process of applying the admixture is omitted.
[0062] Comparative Example 5
[0063] The only difference from Example 2 is that the amount of the admixture is 2.0% of the amount of the main curing agent.
[0064] Comparative Example 6
[0065] The only difference from Example 2 is that the amount of the admixture is 5.0% of the amount of the main curing agent.
[0066] Comparative Example 7
[0067] The only difference from Example 3 is that no admixture is added, and the application of admixture for flocculation and dehydration is omitted.
[0068] The samples of Examples 1-3 and Comparative Examples 1-7 were cured to 3d and 7d ages, and the compressive strength of the samples was measured in accordance with GB / T 50123-2019 "Standard for Geotechnical Test Methods". The test results are shown in Table 2.
[0069] Table 1
[0070]
[0071] Table 2
[0072]
[0073] It can be seen from the test results in Table 2 that the river silt solidified according to the admixtures, main solidifying materials and solidification methods of Examples 1 to 3 has a good solidification effect, and its 3d unconfined compressive strength exceeds 0.35MPa, and can reach a maximum of 0.451MPa; the 7d unconfined compressive strength exceeds 0.65MPa, and can reach a maximum of 0.896MPa.
[0074] By comparing the data of Example 3 and Comparative Example 1, it can be seen that when ammonium sulfate is omitted from the admixture, the unconfined compressive strength of the cured samples 3d and 7d is greatly reduced. This is mainly because after ammonium sulfate is omitted, magnesium silicate cannot react with sulfuric acid to generate magnesium sulfate and colloidal silicon dioxide, resulting in a slow flocculation and precipitation rate, which greatly reduces the flocculation and dehydration effect of the sludge, thereby affecting the subsequent solidification effect of the sludge.
[0075] Comparing the data of Example 2 with Comparative Examples 2 and 3, it can be seen that when steel slag or carbide slag is omitted from the main curing material, the unconfined compressive strength of the cured samples 3d and 7d is greatly reduced. This is mainly because steel slag and carbide slag can generate calcium hydroxide after contacting water, which has an alkali excitation effect on blast furnace slag. Ignoring steel slag or carbide slag leads to insufficient depolymerization and dissolution of active silicon dioxide and active aluminum oxide in blast furnace slag, which in turn affects the curing effect.
[0076] By comparing the data of Example 1 and Comparative Example 4, it can be seen that when 3.0wt% of the admixture is added to the sludge and then solidified, its 3d unconfined compressive strength is about 1.79 times that of the sludge without the admixture, and its 7d unconfined compressive strength is about 1.73 times that of the sludge without the admixture. This shows that in the present invention, the prepared admixture can effectively improve the early strength of the solidified sludge.
[0077] By comparing the data of Example 1, Example 2, Comparative Example 5, and Comparative Example 6, it can be seen that with the increase of the admixture dosage, the 3d and 7d unconfined compressive strengths both show a trend of first increasing and then decreasing, and when the admixture dosage is 3.0-4.0wt% of the main curing material dosage, the early strength is significantly improved. This shows that in the present invention, there is an optimal dosage of the admixture.
[0078] By comparing the data of Example 3 and Comparative Example 7, it can be seen that for river dredged sludge with ultra-high water content (water content greater than 160wt%), the unconfined compressive strength of the sample obtained by directly solidifying the river sludge without using an admixture for flocculation and dehydration is greatly reduced, and it cannot meet the requirements of resource utilization; while by applying an admixture to flocculate and dehydrate the river sludge and then solidify it, the 3d and 7d unconfined compressive strengths can be increased by 10 to 20 times. This shows that in the present invention, the prepared admixture has an efficient flocculation and dehydration effect, and the early flocculation and dehydration process plays an important role in removing pore free water in the river sludge, and has a significant impact on the solidification effect.
[0079] The present invention first uses an admixture to accelerate the flocculation and dehydration speed of river sludge with high water content, and introduces ions such as aluminum ions, calcium ions, and sulfate ions that can promote the generation of ettringite. The main solidifying material is then mixed with the flocculated and dehydrated sludge for solidification. By promoting the rapid generation of ettringite, the early strength of the solidified sludge is greatly improved.
[0080] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A sludge solidification material, characterized in that: The sludge solidification material includes an admixture and a main solidification material; The raw materials of the admixture include, by weight: 18 to 20 parts of magnesium silicate, 15 to 18 parts of aluminum sulfate, 10 to 13 parts of polyferric sulfate, 22 to 26 parts of ammonium sulfate and 24 to 26 parts of quicklime; The raw materials of the main solidifying material include, by weight: 50-70 parts of blast furnace slag, 5-10 parts of steel slag, 15-25 parts of carbide slag and 8-15 parts of phosphogypsum; The mass of the admixture is 3-4 wt % of the mass of the main curing material.
2. The sludge solidification material according to claim 1, characterized in that: The admixture is obtained by mixing magnesium silicate, aluminum sulfate, polyferric sulfate, ammonium sulfate and quicklime according to a mass ratio; the main solidifying material is obtained by mixing blast furnace slag, steel slag, carbide slag and phosphogypsum according to a mass ratio.
3. The use of the sludge solidification material according to claim 1 in solidification of high-water content sludge, characterized in that: The high-water content sludge has a water content of 100-600wt% and an organic matter content of 10-15wt%.
4. A method for solidifying high-water content sludge, characterized in that: Using the sludge solidification material according to claim 1, the method comprises the following steps: The admixture is obtained by mixing magnesium silicate, aluminum sulfate, polyferric sulfate, ammonium sulfate and quicklime according to a mass ratio; The main solidifying material is obtained by mixing blast furnace slag, steel slag, carbide slag and phosphogypsum according to a mass ratio; The admixture is added to the high-water content sludge to obtain pretreated sludge, and then the main solidifying material is added to the pretreated sludge for curing to achieve solidification of the high-water content sludge; The high-water content sludge has a water content of 100-600wt% and an organic matter content of 10-15wt%.
5. The high-water content sludge solidification method according to claim 4, characterized in that: The addition amount of the main solidifying material is 5-15wt% of the wet soil mass in the high-water content sludge.
6. The high-water content sludge solidification method according to claim 4, characterized in that: The curing temperature is 15-30° C., and the relative humidity is >85%.
7. The high-water content sludge solidification method according to claim 4, characterized in that: When the moisture content of the high-moisture sludge is greater than 160wt% and less than or equal to 600wt%, the admixture is added to the high-moisture sludge, stirred and allowed to stand, the supernatant is extracted to obtain pretreated sludge, and then the raw materials of the main solidifying material are added to the pretreated sludge and cured to achieve solidification of the high-moisture sludge.